Research of the Influences of Input Parameters on the Result of Vehicles Collision Simulation - Bogdanović, Vuk; Milutinović, Nenad; Kostić, Svetozar; Ruškić, Nenad (Promet - Traffic&Transportation, 2012)
Vehicle collisions are complex processes which are determined by a large number of different parameters. The development of computer programs for simulation has made the collision analysis and reconstruction procedure easier, as well as the possibility to realise the influences of different parameters on collision processes, which was not possible while using classical methods. The quality of results of vehicle collision simulation and reconstruction is expressed by an error which is determined on the basis of the difference between vehicles stopping positions, which was obtained by the simulation of established vehicles stopping positions in real collisions. Being acquainted with the influence of collision parameters on the simulation error enables the development of more reliable models for automatic optimisation of the collision process and reduction of the number of iterations in the procedure of a collision reconstruction. Within the scope of this paper, the analysis and classification of different collision parameters have been carried out. It has been done by the degree of the influence on the error in the simulation process in the software package Virtual CRASH. Varying twenty different collision parameters on the sample of seven crash tests, their influence on the distance, trajectory and angular error has been analysed, and ten parameters with the highest level of influence (centre of gravity position from front axle of vehicle 1, restitution coefficient, collision place in longitudinal direction, collision place in transverse direction, centre of gravity height-vehicle2, centre of gravity height-vehicle1, collision angle, contact plane angle, slowing down the vehicle and vehicle movement direction) have been distinguished.